Fingerprinting of wheat protein profiles for improved distinction between wheat cultivars and species. Issue 5 (29th July 2020) - Pronin, Darina; Geisslitz, Sabrina; Börner, Andreas; Scherf, Katharina A.
Abstract: Background and objectives: Wheat protein composition is commonly characterized by reversed‐phase (RP)‐HPLC‐UV after extraction of albumins/globulins, gliadins (ω5‐, ω1, 2‐, α‐, and γ‐gliadins), and glutenins (high‐ and low‐molecular‐weight glutenin subunits). However, this traditional classification does not consider the individual distribution of peaks, resulting in loss of information on protein fingerprints. We developed a new approach to peak integration and evaluated its suitability to differentiate between wheat cultivars and species. Findings: Integration events were performed every 20 s, and the relative proportions of the peaks were calculated. We compared the traditional and new integration methods on two sample sets, the first comprising 60 common wheat cultivars from 1891 to 2010 and the second comprising 40 common wheat, spelt, durum wheat, emmer, and einkorn cultivars. The new integration method performed better in differentiating old and modern common wheat cultivars and was also applicable to different wheat species. Conclusions: Unique cultivars were identified that stood out because of their protein composition. Four samples warrant further research to identify the specific proteins that are responsible for the differences. Significance and novelty: The new integration allowed us to map the cultivar‐ and species‐specific fingerprints, identify cultivars with exceptional protein composition, and group similar cultivars.